2018
DOI: 10.1016/j.ajog.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean scar defect: a prospective study on risk factors

Abstract: Based on sonohysterographic examination, maternal body mass index, gestational diabetes, and previous cesarean deliveries are associated with an increased risk for incomplete healing of the uterine incision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 29 publications
2
99
1
1
Order By: Relevance
“…The prevalence of isthmocele was 46.3 %. The prevalence and risk factors of isthmocele from the present data set have been reported previously [13]. In total, 88.4 % (328/371) of participants completed the symptom questionnaire at least once (Fig.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The prevalence of isthmocele was 46.3 %. The prevalence and risk factors of isthmocele from the present data set have been reported previously [13]. In total, 88.4 % (328/371) of participants completed the symptom questionnaire at least once (Fig.…”
Section: Resultssupporting
confidence: 64%
“…This prospective observational cohort study was designed to assess the clinical outcome of isthmocele with respect to bleeding patterns. This study is a continuation of our previous studies, in which the prevalence and risk factors for isthmocele were investigated [12,13]. The study was carried out at Tampere University Hospital, which is a tertiary referral center for highrisk pregnancies, with annual rates of approximately 5000 deliveries and 700 CSs.…”
Section: Methodsmentioning
confidence: 97%
“…However, we found that there was only statistical significance in the univariate analysis in our study. A history of multiple CS procedures was significantly associated with cesarean scar defects, as reported by many other scholars . The possible reason may be that a preexisting CS scar can negatively influence the healing of a new uterine incision due to decreased vascular perfusion and oxygenation in the scar tissue .…”
Section: Discussionmentioning
confidence: 69%
“…However, we only identified a few patients with GDM in the CSP group; thus, we did not include this factor in our study. Other scholars have found that infection, postoperative anemia, and single‐layer uterine closure might contribute to the occurrence of cesarean scar defects . Unfortunately, we were notable to collect this information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation